Handbook on the toxicology of metals (Academic Press, 2007)
Handbook of the Toxicology of Metals is the standard reference work for physicians, toxicologists and engineers in the field of environmental and occupational health. This new edition is a comprehensive review of the effects on biological systems from metallic elements and their compounds. An entirely new structure and illustrations represent the vast array of advancements made since the last edition. Special emphasis has been placed on the toxic effects in humans with chapters on the diagnosis, treatment and prevention of metal poisoning. This up-to-date reference provides easy access to a broad range of basic toxicological data and also gives a general introduction to the toxicology of metallic compounds.